KARAKTERISTIK GULA CAIR YANG DIBUAT DARI PATI UBI GADUNG (Dioscorea hispida D.) DALAM VARIASI JENIS DAN KONSENTRASI ASAM - Fitriani, Reni Okta; Hartiati, Amna; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): September, 2018)
This study aims to know the effect of acid type and concentration on the characteristics of liquid sugar resulting from the hydrolysis of yam gadung ( Dioscorea hispida D.) and the highest DE value from the hydrolysis of the yam gadung starch. This research uses Randomized Block Design of factorial pattern. The first factor is acid treatment consisting of 3 levels: hydrolysis of starch with HNO3, H2SO4, and HCl and second factor is acid concentration consisting of 3 levels: 3%, 4%, and 5% . Each treatment is grouped into 2 based on execution time. The variables observed in this study were total sugar reduction, reducing sugar content, Dextrose Equivalent (DE), clarity, and total dissolved solids. The best treatment determination was done by analysis on DE value of hydrolysis result of yam gadung starch. The treatment of acid type variation was very significant and the acid concentration had a significant effect on the value of DE of hydrolysed yam gadung starch. The best hydrolysis treatment of starchy yam starch is by using chloride acid variation at 3% concentration with Dextrose Equifalent (DE) value of 41,22%. Keywords : starch, yam gadung, hydrolysis, acid